2019
DOI: 10.1016/j.jid.2019.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Association Between the Skin and Oral Microbiota in Atopic Dermatitis

Abstract: Previous studies have shown independently that the skin and gut microbiota are closely associated with atopic dermatitis (AD); however, the microbiota across different habitats of AD patients as an integrated community has not been characterized. In the present study, we comparatively analyzed the structure and function of the microbial communities in the skin, oral cavity, and gut of 172 AD patients and 120 healthy controls through 16S ribosomal RNA gene amplicon sequencing. The skin and oral cavity, but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 41 publications
5
42
0
Order By: Relevance
“…They found that appreciable clinical improvement with antibiotic therapy occurred only in patients whose AD lesions were infected by S. aureus at a density of greater than 10 6 colony‐forming units per cm 2 . Similarly, microbiome studies of paediatric patients with AD show that the relative abundance of S. aureus is associated with disease flares and correlates with severity …”
Section: Staphylococcus Aureus Colonization In Atopic Dermatitismentioning
confidence: 99%
“…They found that appreciable clinical improvement with antibiotic therapy occurred only in patients whose AD lesions were infected by S. aureus at a density of greater than 10 6 colony‐forming units per cm 2 . Similarly, microbiome studies of paediatric patients with AD show that the relative abundance of S. aureus is associated with disease flares and correlates with severity …”
Section: Staphylococcus Aureus Colonization In Atopic Dermatitismentioning
confidence: 99%
“…The relationship between microbiomes across different body sites has recently been investigated in patients with AD. Li et al [17] revealed differential alterations in community-level diversity between microbiomes from the same body habitats (alpha diversity) of patients with AD and healthy controls in a study comparing the structure and predicted functions of microbial communities from the skin, oral cavity, and gut. In patients with AD, the skin showed the most significant decrease in alpha diversity, followed by the oral cavity, whereas no differences in community structure were detected for the gut microbiome [17].…”
Section: Key Pointsmentioning
confidence: 99%
“…Li et al [17] revealed differential alterations in community-level diversity between microbiomes from the same body habitats (alpha diversity) of patients with AD and healthy controls in a study comparing the structure and predicted functions of microbial communities from the skin, oral cavity, and gut. In patients with AD, the skin showed the most significant decrease in alpha diversity, followed by the oral cavity, whereas no differences in community structure were detected for the gut microbiome [17]. Differences in the extent of diversity between different habitats (beta diversity) were observed, with the microbial lineage between the skin and oral cavity being closer in patients with AD than in healthy controls.…”
Section: Key Pointsmentioning
confidence: 99%
“…TSLP-induced allergic Th2/Th17 polarization likely depends on dectin-2emediated allergen sensitization and upregulation of Th2/Th17-related cytokines. Han et al, 2017;Li et al, 2019Liang et al, 2019;Sun et al, 2011;Yu et al, 2019;Leprosy Variants of genes in the NOD2-mediated signaling pathway are associated with susceptibility to infection with M. leprae. HLA-B*13:01 was associated with the development of the dapsone hypersensitivity syndrome.…”
Section: Supplementarymentioning
confidence: 99%